2014
DOI: 10.1007/s00467-014-2866-8
|View full text |Cite
|
Sign up to set email alerts
|

Viral surveillance and subclinical viral infection in pediatric kidney transplantation

Abstract: The more potent immunosuppressive therapy that has successfully reduced the incidence of acute rejection and improved graft outcomes has also resulted in a higher incidence of viral complications. Sensitive molecular methods now allow for the detection of subclinical viral infection which is increasingly recognized due to the adoption of routine post-transplant viral surveillance protocols. The goal of viral surveillance is the detection of subclinical viral infection that triggers an intervention; one that ei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
12

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 58 publications
3
42
0
12
Order By: Relevance
“…In our center, PTLD has been diagnosed in seven of the 252 RTx patients (3.7 %) and four of these had received their kidney graft as infants. Excellent articles on the management of CMV, EBV, and PV infections have recently been published [57][58][59][60][61].…”
Section: Infectionsmentioning
confidence: 99%
“…In our center, PTLD has been diagnosed in seven of the 252 RTx patients (3.7 %) and four of these had received their kidney graft as infants. Excellent articles on the management of CMV, EBV, and PV infections have recently been published [57][58][59][60][61].…”
Section: Infectionsmentioning
confidence: 99%
“…We therefore pooled the data Defined as eGFR (28) at 30 days posttransplant. 3 Within the first year posttransplant. 4 Including borderline changes (Banff 97 '09 update [26,27] …”
Section: Impact Of Immunosuppressive Therapy On CMV Disease and Replimentioning
confidence: 99%
“…Despite recent advances achieved in antiviral therapy, cytomegalovirus (CMV) remains the most important opportunistic infectious agent in transplant recipients, because CMV replication is associated with high morbidity, mortality, and diminished graft survival (1)(2)(3)(4)(5)(6)(7)(8)(9). Experimental data indicate that mammalian target of rapamycin inhibitors (mTORi) such as everolimus (EVR) and sirolimus (SRL) exhibit direct anti-CMV effects leading to reduced CMV replication (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Experience with pediatric kidney transplant recipients suggests a 67 % incidence of CMV infection, with approximately 67 % being negative at the time of transplantation [115]. The direct and indirect effects of CMV infection result in a significant morbidity and mortality among kidney transplant recipients.…”
Section: Herpes Viruses: Cytomegalovirusmentioning
confidence: 98%
“…Oral valganciclovir is recommended for CMV prophylaxis posttransplant [118]. Duration of chemoprophylaxis is dependent on the serostatus of the donor and recipient [115]. While it is effective in reducing the incidence of symptomatic CMV, prospective viral surveillance studies have shown subclinical infection in 12-22 % of pediatric kidney transplant recipients, hence the importance of viral surveillance [115].…”
Section: Herpes Viruses: Cytomegalovirusmentioning
confidence: 99%